Konsep Zakat dalam Perspektif Fikih Islam: Kajian tentang Syarat, Rukun, Nisab dan Haul - Surya Bakti; Putri Zahara Siregar; Rima Annisa; Rosa Planturia; Rizky Bunga Ananda; Siti Maimunah (Journal of Contemporary Gender and Child Studies, 2026)
Zakat is one of the pillars of Islam that plays an important role in the lives of Muslims, both as an act of worship and as an instrument of social welfare. However, public understanding of the concepts, requirements, pillars, nisab, haul, and distribution of zakat still needs to be improved to ensure its implementation is in accordance with Islamic law. This study aims to analyze the concept and implementation of zakat from the perspective of Islamic jurisprudence and examine its role in improving social welfare. This research employs a library research method with a descriptive qualitative approach. Data were collected through documentation studies from books, scientific journals, and other relevant literature, and analyzed using content analysis techniques. The results indicate that zakat has interconnected spiritual and social functions. Its implementation must fulfill specific requirements and pillars and be based on the provisions of nisab and haul. Furthermore, the proper distribution of zakat to eligible recipients (mustahik) can help reduce social inequality and improve community welfare. Therefore, zakat serves not only as a religious obligation but also as an instrument for economic empowerment and social development within Muslim communities.